Analysis of the Filter Bubble Algorithm on TikTok Concerning 'Toxic' Polarization During the 2024 Presidential Campaign - Ruhyat, Ruhyat; Wahidin, Danis Tri Saputra (Borong Newinera Publisher, 2024)
Social media is a platform for everyone to express and convey information. The emergence of social media certainly affects the behavior of each individual who uses it. This is due to a social media algorithm called the filter bubble, which can lead to polarization as in the Tiktok application and several other social media applications. Simply put, we are made to feel as if we know everything that is happening around us, when in fact we do not. This is what causes 'toxic' polarization to form an ignorant personality. In other words, 'toxic polarization' will isolate every social media user intellectually. Of course, this will be very dangerous if it happens during the 2024 presidential election campaign because it will cause many divisions. The long-term effect will certainly affect democracy so that it can cause stagnation.